Home-Based Management of Patients With Cancer Experiencing Treatment-Induced Toxicities With a Nurse-Led Telephone Triage (the NTT Study). Issue 1 (January 2022) - Calvetti, Lorenzo; Tealdo, Marta; Simionato, Francesca; Pagiusco, Gaetana; Cimenton, Roberta; Gasparin, Barbara; Corà, Francesco; De Vivo, Rocco; Merlini, Laura; Aprile, Giuseppe
Abstract : PURPOSE: Novel organization models ensure early management of treatment-related adverse events (TRAEs) of new anticancer drugs. The aim of this prospective observational study was to evaluate the impact of the introduction of a nurse-led telephone triage (NTT) in reducing hospitalization of patients with cancer (CPs). PATIENTS AND METHODS: CPs on active medical treatment were educated to call the NTT in case of symptoms or TRAEs. Assessment of TRAEs was performed by trained oncology nurses according to the Common Terminology Criteria for Adverse Events grading scales and subsequent actions were taken according to the severity of the events. The primary end point of the study was to compare the rate of hospitalization of CPs on anticancer treatment after the introduction of NTT with that of the 2017-2018 period. RESULTS: From September 2018 to September 2019, a total of 1, 075 patients received systemic anticancer treatment ( v 936 patients in the same 2017-2018 period). Total consultations at NTT were 429 and 581 TRAEs were reported. Notably, 117 patients reported more than one TRAE. Common Terminology Criteria for Adverse Events were graded as G1 (237, 40.8%), G2 (231, 39.8%), or G3-4 (113, 19.4%). In the observation period, 109 CPs on treatment were hospitalized versus 138 in the 2017-2018 period with a normalized hospitalization rate of 10.1% versus 14.7% ( P = .002 chi-square) with a reduction in normalized number of hospitalization of 44 and an estimated cost savings of 345, 246 euros. CONCLUSION: The implementation of the NTT system in the clinical practice may help reducing the rates of hospitalization through the emergency room of CPs receiving modern medical treatments.